Cultivating a culture of nonviolence in early childhood development centers and schools - Taukeni, Simon George, 1973- (IGI Global, Information Science Reference, an imprint of IGI Global, 2019)
"This book expands on multicultural nonviolent teaching techniques in early childhood development centers, schools, institutions of high learning and centers of teacher development and training to understand nonviolence concepts, its techniques, and its application to achieve desired conducive environment outcomes"- Resumé vydavatel
"Premier reference source."
Keywords: předškolní výchova -- sociální aspekty; etická výchova; nenásilí; studium a výuka; násilí ve škole; preschool education -- social aspects; ethical education; nonviolence; study and teaching; school violence; elektronické knihy; monografie; electronic books; monographs